How much is a coin worth: acute pancreatitis, suspected pancreatic cancer, and a Whipple surgery caused by ingestion of a coin? - Altan, Ege; Kav, Taylan (Gastroenterology Review/Przegląd Gastroenterologiczny, 2021)
Acute pancreatitis caused by the ingestion of foreign objects is rarely reported in the literature. Oedema in the duodenal papilla, obstruction of the Wirsung canal, and increased reflux of the duodenal contents into the pancreas have been held responsible in these cases [1–3]. Acute pancreatitis can sometimes mimic pancreas cancer [4]. However, we have seen no other cases in the literature in which a foreign body, a coin, caused acute pancreatitis that mimiced a tumour around the proximal common bile duct.